1999
DOI: 10.1097/00005537-199906000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lateral osteotomies in the dimensions of the nasal cavity

Abstract: After lateral and medial ostetomies a significant decrease in the anterior dimensions of the nose is observed. The decrease following osteotomy does not seem to be due to the placement of the lateral osteotomy at the pyriform aperture but rather to the detachment of the bony vault from the surrounding structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…The dimensions of the nasal valve, and how it changes with osteotomies, have been measured by several groups. [6][7][8] To our knowledge, this is the first study to observe the quantitative changes that lateral nasal osteotomies produce on the exterior nasal esthetic. An extensive search of the literature has not revealed a previous study examining this topic.…”
Section: Commentmentioning
confidence: 91%
“…The dimensions of the nasal valve, and how it changes with osteotomies, have been measured by several groups. [6][7][8] To our knowledge, this is the first study to observe the quantitative changes that lateral nasal osteotomies produce on the exterior nasal esthetic. An extensive search of the literature has not revealed a previous study examining this topic.…”
Section: Commentmentioning
confidence: 91%
“…13 Guyuron similarly found that osteotomies constricted the nasal airway in the majority of cases, with the most signifi cant airway narrowing found in patients with anteriorly positioned inferior turbinates and signifi cantly medializing osteotomies. 14 To reduce the risk of airway narrowing, osteotomies should be relatively conservative, and the soft tissue attachments of the nasal bones and upper lateral cartilages should be preserved ( Fig.…”
Section: Autospreader Grafts/spreader Flapsmentioning
confidence: 94%
“…13 Dorsal reconstruction with an autologous rib graft can also support the upper lateral cartilages and the middle vault.This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
mentioning
confidence: 99%
“…A 2004 review by Lal and Corey [61 •• ] outlined these uses. In addition to measuring the effect of septal deviations [29] and osteotomies [49], expanded uses include turbinate procedures, nasal-valve reduction and rhinoplasty [29,30,44,[46][47][48][49]60]. Reconstructive procedure evaluation has been utilized for cleft lip and palate, antrochoanal atresia and maxillofacial expansion procedures [31,[50][51][52].…”
Section: Techniques Available To Assess Nasal Obstructionmentioning
confidence: 99%